Analisis Jejaring Wacana Rancangan Undang-Undang Kesehatan Tahun 2023 dan Potensi Judicial Review ke Mahkamah Konstitusi - Kurniawati, Heryna Oktaviana (UNES Law Review, 2024)
The formation of legislation in Indonesia has been regulated through Law Number 12 of 2011 concerning the Formation of Legislative Regulations, where formal and material principles must be fulfilled so that they do not have the potential to become the object of formal review and the object of material review after being ratified by the Republic of Indonesia's House of Representatives Indonesia. The Draft Health Law for 2023 which was passed by the DPR RI received rejection from various parties. It has the potential for Discourse Network Analysis to be utilized in legal research to map the potential for judicial review of the health bill. Arguments expressed by actors through reporting in the digital mass media detik.com. From 42 valid news stories, 120 statements, 34 discourses (concepts) and 35 actors. The results obtained are that the discourse "Public participation is a consideration for ratifying the health bill" is the dominant discourse. Conflicts between actors indicate the principle of openness as a formal requirement for the formation of legislation is not fulfilled. After ratification of Law Number 17 of 2023 concerning Health, it has the potential to be submitted as an object of formal and material review to the Constitutional Court.